Digitalisasi Prasasti dan Pelinggih Desa Baturan Gianyar Berbasis Augmented Reality Based Marker - Sarasvananda, Ida Bagus Gede; Aditama, Putu Wirayudi; Iswara, Ida Bagus Ary Indra; Desnanjaya, I Gusti Made Ngurah (SINTECH (Science and Information Technology) Journal, 2023)
Digitalization of the inscriptions and shrines of Batuan Gianyar Village based on Augmented Reality (AR) Markers is an innovative project that aims to preserve, promote and revive the cultural and historical heritage of Baturan Village, Gianyar, Indonesia, through the application of Augmented Reality technology. Baturan Village is known to have inscriptions and pelinggih which have high historical value. This research uses AR Marker technology to connect the physical world with digital content. The inscriptions and shrines of Baturan Village are marked with AR markers which allow users to access additional information about these objects via mobile devices. This AR application provides an immersive and interactive experience, allowing users to explore the history and meaning of inscriptions and shrines. The method used in developing this AR application is R & D. The results of this research after testing loading time using four different smartphones, Xiaomi Note8 Pro and iPhone 13, have a faster average loading time response compared to other smartphones.